Performance evaluation of forward osmosis membranes for desalination applications - Mohd Amirul Mukmin, Abdullah; Nur Aisyah, Shafie; Mazrul Nizam, Abu Seman; Syamsul Bahari, Abdullah (Chiangmai University, 2024)
Forward osmosis (FO) has become a technology with great potential for numerous applications, including water desalination. One of the critical factors in determining the FO performance is the selection of the appropriate membrane material that compatible with draw solution. In this study, commercial cellulose triacetate (CTA) and aquaporin-based membranes, as well as a fabricated PES/PVP membrane, were used, with 1-Butyl-3-methylimidazolium tetrafluoroborate ([Bmim][BF4]) as the thermo-responsive ionic liquid (TRIL) draw solution. The bench scale of FO system was setup upon co-currently flow rate of 60.0 mL/ min at room temperature. The 7 % PVP with 15 % PES had the best performance, with the highest water flux (Jw) (4.93 LMH), lowest reverse solute diffusion (RSD) (0.43 gMH). The fabricated membrane demonstrated a significantly higher performance compared to the commercial aquaporin-based FO membrane, with an improvement of approximately 60%.